A política de accountability educacional na rede municipal de ensino de Fortaleza: a ênfase na avaliação externa - Souza, Maria Rosângela de (2021)
This research addressed the policy of educational accountability in the education system in the city of Fortaleza, with an emphasis on external evaluation in the period from 2013 to 2019. The accountability model has been present in the policies of several countries, and in Brazil, for decades. 2005 starts to have an accountability system in basic education, with the Education Development Index (IDEB) an accountability indicator in the country. Accountability has its intrinsic nature with evaluation, accountability and accountability, maintaining dialecticity with each dimension according to the transformations and/or reforms of the State, which follows the line of neoliberal ideals and thus legitimizes the accountability policy in education from the requirement of external evaluation as support in obtaining results. The State of Ceará, through the Secretariat of Education (SEDUC) has been implementing large-scale external evaluation for decades, such as the Permanent System of Evaluation of Basic Education of Ceará (SPAECE), as well as advancing more and more with each edition IDEB reaching the stated goals, even surpassing them, which gives it prominence at the national level. Thus, the objective of this research was to analyze the accountability policy, with an emphasis on external evaluation in basic education in the city of Fortaleza. The theoretical foundation was based on contributions from: Afonso (2009, 2010, 2011, 2012, 2013, 2014), Mészáros (2008), Horta Neto (2007, 2014, 2015, 2017), Shiroma and Evangelista (2012), Freitas (1995, 2016), Karl Marx (1977, 2010, 1985, 2017), Schneider and Nardi (2019), among others. The central issue of this research was: when emphasizing external evaluation as an instrument of educational accountability policy for the municipal education system in Fortaleza, what are the present interests? For this purpose, we resorted to historical-dialectical materialism, as it is understood from a perspective that reality is based on the historicity of its subjects, making this study based on bibliographical and documentary research. In conclusion, it can be inferred that, through the policy of accountability, the municipal education system in Fortaleza is in line with commercial interests, whose education process is reduced to evaluations and exposure of numbers, thus diverting the ultimate purpose of education which is humanization.